1998
DOI: 10.1007/s002130050745
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that GABA transmission mediates context-specific extinction of learned fear

Abstract: Six experiments used rats to study the effects of the beta-carboline FG 7142 on extinction of fear responses (freezing) to an auditory cue that had signalled footshock. Subcutaneous injection of FG 7142 interfered with the development of extinction without having any detectable effect on the rats' levels of fear prior to extinction. Injection of FG 7142 also reversed extinction, partially reinstating fear responses that had been extinguished previously. A similar reinstatement of extinguished fear was seen whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 31 publications
13
159
1
Order By: Relevance
“…In the remaining rats there was significantly more freezing during CS presentations as compared to the pre-CS period (M pre-CS freezing ϭ 5.5, SEM ϭ 2.4), F(1, 17) ϭ 75.8, p Ͻ .05. In contrast to Experiment 1, there was no evidence for summation in freezing during the first Stage II trial: freezing during the first presentation of the compound CS was not significantly different to the average responding observed to the individual CSs at the end of Stage I,F(1,20) It is possible that the difference between group over -vehicle and group over -FG7142 was due not to FG7142 attenuating expression of overexpectation, but rather to it attenuating expression of any extinction learning that might have occurred across the four nonreinforced CS presentations on test (Harris & Westbrook, 1998). To further examine this possibility, test performances across CS presentations were analyzed (see Figure 3).…”
Section: Resultsmentioning
confidence: 89%
“…In the remaining rats there was significantly more freezing during CS presentations as compared to the pre-CS period (M pre-CS freezing ϭ 5.5, SEM ϭ 2.4), F(1, 17) ϭ 75.8, p Ͻ .05. In contrast to Experiment 1, there was no evidence for summation in freezing during the first Stage II trial: freezing during the first presentation of the compound CS was not significantly different to the average responding observed to the individual CSs at the end of Stage I,F(1,20) It is possible that the difference between group over -vehicle and group over -FG7142 was due not to FG7142 attenuating expression of overexpectation, but rather to it attenuating expression of any extinction learning that might have occurred across the four nonreinforced CS presentations on test (Harris & Westbrook, 1998). To further examine this possibility, test performances across CS presentations were analyzed (see Figure 3).…”
Section: Resultsmentioning
confidence: 89%
“…This indicates that FG-7142 did not nonspecifically increase the fear response, but rather 'selectively reversed the component of extinction linked to the environmental context where extinction training had occurred'. 156 This effect could not be explained by state dependency. Thus, it appears that GABA is involved in the expression of extinction in a contextdependent manner.…”
Section: Neurotransmitter Systemsmentioning
confidence: 96%
“…The major inhibitory neurotransmitter in the mammalian brain, g-aminobutyric acid, seems to figure prominently in the development and expression of fear extinction. Harris and Westbrook 156 demonstrated that FG-7142, an inverse agonist of the GABA A receptor that functionally decreases GABA transmission, dose-dependently impaired within-session extinction and, when administered before test, blocked extinction retention in the context of extinction training, but had no effect on performance in a novel context. That is, both vehicle-treated and FG-7142-treated animals showed equal renewal of the fear response when tested outside of the extinction context.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…Several studies support the central role GABA neurotransmission has in extinction, however, there are different reports regarding the role of GABA in extinction (Harris and Westbrook, 1998;Marsicano et al, 2002;McGaugh et al, 1990;Pereira et al, 1988Pereira et al, , 1989Shumyatsky et al, 2002). Systemic administration of the GABA A antagonist picrotoxin after the extinction of inhibitory avoidance learning enhanced extinction retention during testing (McGaugh et al, 1990), and the GABA A -positive allosteric modulator diazepam impaired extinction retention when administered before extinction in a shuttle avoidance task (Pereira et al, 1989).…”
Section: Gaba a In Amygdala And Cta Extinctionmentioning
confidence: 99%
“…In view of this point, Harris and Westbrook (1998) demonstrated that systemic injection of the beta-carboline FG 7142 (a GABA A inverse agonist) before extinction training attenuated both the acquisition and the expression of fear memory extinction. However, here muscimol was infused immediately following the first extinction session, hence, during the time window of stabilization of the memory trace (ie, consolidation).…”
Section: The Importance Of Gaba In Expression and Consolidation Of Exmentioning
confidence: 99%